Nursing care of the female patient with diagnosed amniotic fluid embolism during the Caesarean section in the spinal anesthesia — a case report - Jendretzki, Andrzej; Mędrzycka-Dąbrowska, Wioletta; Kwiecień, Katarzyna (Nursing Problems / Problemy Pielęgniarstwa, 2012)
Introduction. Amniotic fluid embolism is a rare, but serious complication, frequently leading to death of a delivering woman. The pathophysiology of the amniotic fluid embolism is multifactorial in origin and still remains poorly understood. Aim of the study. The purpose of the study was to nursing diagnoses for a female patient with amniotic fluid embolism during the caesarean section in the spinal anaesthesia and afterwards on the intensive care unit hospitalization. Materials and methods. The research is based on the professional clinical case report and has retrospective character. Data was collected on the basis of patient’s medical history and analysis of patient’s medical documentation — medical history, anaesthesia card, nursing process and laboratory tests results. Results and conclusions. All the diagnosed problems have been fully and successfully resolved. The remaining nursing problems had to be treated by nursing staff after moving the patient from the intensive care unit to next stages of hospitalization.